Enhanced autophagy induction via the mitochondrial delivery of methylated β-cyclodextrin-threaded polyrotaxanes using a MITO-Porter. Issue 50 (5th June 2019) - Yamada, Yuma; Daikuhara, Shinnosuke; Tamura, Atsushi; Nishida, Kei; Yui, Nobuhiko; Harashima, Hideyoshi
Abstract : Failure of autophagy induction results in the accumulation of abnormal mitochondria to cause neurodegenerative diseases. Abstract : Failure of autophagy induction results in the accumulation of abnormal mitochondria to cause neurodegenerative diseases. Artificial autophagy activation via the mitochondrial delivery of polyrotaxane with autophagy induced activity is achieved using a MITO-Porter, a nanodevice for mitochondrial delivery. This strategy can be applied to innovative research and therapy.